LncRNA-NEAT1 Sponges miR-128 to Promote Inflammatory Reaction and Phenotypic Transformation of Airway Smooth Muscle Cells. (17th January 2022) - Song, Danyang; Jiang, Yajing; Zhao, Qiuju; Li, Jinling; Zhao, Yuqi
Abstract : Objective . Pediatric asthma is still a health threat to the children. Long noncoding RNA-NEAT1 (lncRNA-NEAT1) was reported to be positively correlated with the severity of asthma. We aimed to study the effects and mechanism of lncRNA-NEAT1on inflammatory reaction and phenotypic transformation of airway smooth muscle cells (ASMCs) in the bronchial asthma. Method . The degree of lncRNA-NEAT1 and miR-128 mRNA in children with bronchial asthma and healthy individuals was tested by qRT-PCR. After the inflammatory reaction and phenotypic transformation of PDGF-BB-induced ASMCs, the expression of lncRNA-NEAT1 or miR-128 in the AMSC was disturbed in the AMSC. Subsequently, the expression of lncRNA-NEAT1 and miR-128 was detected by the way of qRT-PCR, and western blot was applied to measure the expression of MMP-2, MMP-9, α -SMA, calponin, NF- κ B, and so on in the cells. The content of TNF- α, IL-1 β, IL-6, and IL-8 in the cell culture supernatant was checked by ELISA. MTT, Transwell, and flow cytometry were used to detect cell proliferation, migration, and apoptosis. Further, the targeting relations between lncRNA-NEAT1 and miR-128 were evaluated by the dual-luciferase reporter assay. Result . In the sputum of children with bronchial asthma, lncRNA-NEAT1 was significantly upregulated while miR-128 was rapidly downregulated. Besides, lncRNA-NEAT1 and miR-128 were competitively combined and, for their expression, negatively correlated. Conclusion . lncRNA-NEAT1 sponges miR-128 to boost PDGF-BB-induced inflammatory reaction and phenotypic transformation of ASMCs to aggravate the occurrence and development of childhood bronchial asthma.